Metabolic syndrome in type 2 diabetic patients: a review of current evidence - Regufe, Virgínia M.G. (2020)
The metabolic syndrome (MS) is a set of metabolic disturbances, represented by various cardiovascular risk factors which are generally associated with the central accumulation of fat and the resistance to insulin. Inadequate changes in eating behaviours and weight loss, which are associated to taking part in regular physical activity, are considered to be primary and first choice therapies for the treatment of MS, as they assist in the reduction of the abdominal girth and visceral fat, improve the sensibility to insulin and reduce the plasmatic concentrations of glucose and triglycerides, raise the values of high density lipoproteins and, consequently decrease the risk factors which contribute to the development of type 2 diabetes. The MS is a current discussion theme in the health field as it is related to illnesses/diseases, which not only cause a worldwide high mortality rate but show increasing incidence. Type 2 diabetes is characterised by a deregulation of the carbohydrates, lipids and proteins found in the metabolism and result in diminished secretion of insulin, resistance to insulin or a combination of both. Type 2 diabetes is the most form of diabetes of the first 3 types of diabetes, representing 90% of all cases. Diabetes is a chronic and complex disease which requires a strict medical follow-up so as to reduce the risks and obtain strategies for its control. The fast-epidemiological global evolution which has been registered in the last few years, leads to it being considered one of the pandemics of the 21st century. In this non-systematic and advanced review of the MS in type 2 diabetic patients, several articles were consulted, and some recently published studies were analysed.